2020
DOI: 10.1101/2020.02.15.950444
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

WDR90 is a centriolar microtubule wall protein important for centriole architecture integrity

Abstract: 27Centrioles are characterized by a nine-fold arrangement of long-lived 28 microtubule triplets that are held together by an inner protein scaffold. These 29 structurally robust organelles experience strenuous cellular processes such as cell 30 division or ciliary beating while performing their function. However, the molecular 31 mechanisms underlying the stability of microtubule triplets, as well as centriole 32 architectural integrity remain poorly understood. Here, using ultrastructure expansion 33 microsco… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…The molecular basis for that binding has previously been unknown, but the findings here provide models for this interaction. Given that another cylindrical layer containing WDR90 is proposed to lie between the FAM161A layer and microtubules ( Steib et al , 2020 ), FAM161A may only be able bind microtubules through gaps in the WDR90 layer. This might explain how evolution has produced small microtubule-binding domains of short loops and helices ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…The molecular basis for that binding has previously been unknown, but the findings here provide models for this interaction. Given that another cylindrical layer containing WDR90 is proposed to lie between the FAM161A layer and microtubules ( Steib et al , 2020 ), FAM161A may only be able bind microtubules through gaps in the WDR90 layer. This might explain how evolution has produced small microtubule-binding domains of short loops and helices ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the existence of a cylindrical sheet of material running along the centriole lumen and connecting all the A-tubules (Geimer & Melkonian 2004, Vorobjev & Chentsov 1982. Indeed, along the centriole length, the pinhead is replaced by an inner centriole scaffold that is involved in stabilizing the centriole barrel (Le Guennec et al 2021, Steib et al 2020) (Figure 1c). Recently, Le Guennec and colleagues (2020) described its ultrastructural organization (Figure 1c), revealing the evolutionary conservation of the inner scaffold despite its species-specific differences.…”
Section: Attaching the Microtubule Tripletsmentioning
confidence: 99%
“…Centrioles are not just hollow, empty barrels; instead, about 70% of their lumen contains an inner helical scaffold that forms a dense lattice by interconnecting the microtubule triplets [15,26]. Recent studies suggested structural functions for the inner core in the maintenance of centriole microtubule triplet cohesion and geometry [15,27]. Application of Ultrastructure Expansion Microscopy (U-ExM) to the centriole inner core identified and mapped POC5, POC1B, Centrin-2, FAM161A and WDR90 as the five components of a microtubule-associated complex associated with the helical scaffold [27].…”
Section: Centrosomesmentioning
confidence: 99%
“…Recent studies suggested structural functions for the inner core in the maintenance of centriole microtubule triplet cohesion and geometry [15,27]. Application of Ultrastructure Expansion Microscopy (U-ExM) to the centriole inner core identified and mapped POC5, POC1B, Centrin-2, FAM161A and WDR90 as the five components of a microtubule-associated complex associated with the helical scaffold [27]. In addition to the inner core, the molecular and structural code of the distal appendages were also unraveled by with nanoscale precision [23,25,28].…”
Section: Centrosomesmentioning
confidence: 99%